Comparison of Efficacy Between Transabdominal and Transthoracic Surgical Approaches for Siewert Type II Adenocarcinoma of the Esophagogastric Junction: A Systematic Review and Meta-Analysis - Li, Zonglin; Jiang, Huaiwu; Chen, Jin; Jiang, Yifan; Liu, Yi; Xu, Linxia (Frontiers in Oncology, 2022)
Background: The optimal surgical approach, whether transabdominal (TA) or transthoracic (TT), for Siewert type II adenocarcinoma of esophagogastric junction (AEG) remains controversial. This study aims to compare the efficacy of TA and TT surgical approaches for Siewert type II AEG. Methods: Studies comparing the surgical and oncological outcomes of TA and TT surgical approaches for Siewert type II AEG up to June 2021 were systematically searched from Web of Science, PubMed, Embase and Cochrane Library. A pooled analysis was performed for the available data regarding the baseline features, surgical and oncological outcomes. The RevMan 5.3 software was used to perform the statistical analysis. Quality evaluation and publication bias were also conducted. Results: Twelve studies with a total of 2011 patients, including 985 patients in the TA group and 1026 patients in the TT group, were included in this study. In the pooled analysis, the surgical outcomes including operative time (MD = −54.61, 95% CI = −123.76 to 14.54, P = 0.12), intraoperative blood loss (MD = −28.85, 95% CI = −71.15 to 13.46, P = 0.18), the number of dissected lymph nodes (MD = 1.90, 95% CI = −1.32 to 5.12, P = 0.25), postoperative complications (OR = 0.84, 95% CI = 0.65 to 1.07, p = 0.16), anastomotic leakage rate (OR = 1.02, 95% CI = 0.63 to 1.65, p = 0.93) as well as postoperative death rate (OR = 0.89, 95% CI = 0.46 to 1.72, p = 0.73), and the oncological outcomes including overall recurrence rate (OR = 0.75, 95% CI = 0.37 to 1.50, p = 0.41), 3-year overall survival (OS) rate (OR = 1.19, 95% CI = 0.54 to 2.65, p = 0.66) as well as 5-year OS rate (OR = 1.21, 95% CI = 0.84 to 1.74, p = 0.30) of the two groups were all comparable. Conclusions: Both TA and TT surgical approaches are acceptable for Siewert type II AEG, and one offers no significant advantage over the other in terms of short- and long-term outcomes. However, more high-quality randomized controlled trials are needed to confirm this conclusion.